THE CULTURAL REPRESENTATION OF DISABLED WOMEN IN MALAYSIA - Amin, Aizan Sofia (International Journal of Psychosocial Rehabilitation, 2020)
--This paper sets to explore how disabled women in Malaysia are being perceived in society. The data of this study was collected from in-depth interviews with 33 Malaysian women with physical (mobility) impairment. Over a period of 6 months, 17Malays, 8 Chinese and 8 Indian women were interviewed twice in Malaysia. The majority of informants came from low income and rural families and thus many of them had limited access to basic living needs; such as healthcare, transportation, education and training, as well as employment. Being disabled in Malaysia is complicated by the fact that there are very few positive public role models. Not only are disabled people rarely seen on the street, they are also almost entirely absent from the media, television, or other forms of public life. Living in a society that has very low representation of positive disabled role models in the public and media, and also a persistent negative cultural representation of disabled people, have made many disabled women developed low self-esteem. Many of them were systematically excluded from full participation in society. They spent much of their time within their home environment because many of them lived in remote areas and living in poverty. The family played a key role for them and they had very limited contact with the wider population (both disabled and nondisabled people) so their recognition was almost totally absent in public. Therefore, further discussion on these aspects will be discussed in this paper.